2022
DOI: 10.1227/neu.0000000000001927
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical Performance in the First 2 Years of Merit-Based Incentive Payment System: A Descriptive Analysis and Predictors of Receiving Bonus Payments

Abstract: BACKGROUND:The merit-based incentive payment system (MIPS) program was implemented to tie Medicare reimbursements to value-based care measures. Neurosurgical performance in MIPS has not yet been described. OBJECTIVE: To characterize neurosurgical performance in the first 2 years of MIPS. METHODS: Publicly available data regarding MIPS performance for neurosurgeons in 2017 and 2018 were queried. Descriptive statistics about physician characteristics, MIPS performance, and ensuing payment adjustments were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Other variables that were positively associated with MIPS performance included participation in MIPS as a physician group or APM and average HCC risk score of beneficiaries. The positive association between group or APM participation and performance has been extensively reported across multiple specialties, 31-37 including neurosurgery 25 ; this finding may be related to APM practices having improved infrastructure and resources for collecting and reporting performance measures. 18 The positive association between HCC risk score and performance may be partly explained by the incorporation of risk adjustment measures in later years of the program, such as the inclusion of the risk-adjusted cost subscore in 2018 and 2019 and the introduction of the CPB in 2020.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Other variables that were positively associated with MIPS performance included participation in MIPS as a physician group or APM and average HCC risk score of beneficiaries. The positive association between group or APM participation and performance has been extensively reported across multiple specialties, 31-37 including neurosurgery 25 ; this finding may be related to APM practices having improved infrastructure and resources for collecting and reporting performance measures. 18 The positive association between HCC risk score and performance may be partly explained by the incorporation of risk adjustment measures in later years of the program, such as the inclusion of the risk-adjusted cost subscore in 2018 and 2019 and the introduction of the CPB in 2020.…”
Section: Discussionmentioning
confidence: 78%
“…This finding aligns with previous literature showing that physicians with higher proportions of dual-eligible beneficiaries had lower MIPS scores, were more likely to receive negative payment adjustments, 18,19,23,24 and were less likely to receive bonuses. 25 Year variables and the interaction between year and safety-net status were positively associated with MIPS performance, suggesting that providers improved their performance over successive years of the program, with safety-net providers improving at a faster rate than non–safety-net providers. The accelerated improvement of safety-net providers may explain the finding that safety-net providers had a higher mean score than non–safety-net providers by 2020.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…12 However, a recent article showed that neurosurgeons who take care of socially disadvantaged patients are penalized under performance reimbursement methods. 13…”
mentioning
confidence: 99%
“…There is ample evidence to support this. Neurosurgeons who treat a large portion of Medicaid patients fared worse in the Merit-Based Incentive Performance System 6 and Medicaid patients had worse outcomes in the Quality Outcomes Database. 7 Safety-net hospitals are consistently penalized under value-based reimbursement.…”
mentioning
confidence: 99%